Breadth of Antibodies to Plasmodium falciparum Variant Surface Antigens Is Associated With Immunity in a Controlled Human Malaria Infection Study - Kimingi, Hannah W.; Kinyua, Ann W.; Achieng, Nicole A.; Wambui, Kennedy M.; Mwangi, Shaban; Nguti, Roselyne; Kivisi, Cheryl A.; Jensen, Anja T. R.; Bejon, Philip; Kapulu, Melisa C.; Abdi, Abdirahman I.; Kinyanjui, Samson M.; et al. (Frontiers in Immunology, 2022)
Background: Plasmodium falciparum variant surface antigens (VSAs) contribute to malaria pathogenesis by mediating cytoadhesion of infected red blood cells to the microvasculature endothelium. In this study, we investigated the association between anti-VSA antibodies and clinical outcome in a controlled human malaria infection (CHMI) study. Method: We used flow cytometry and ELISA to measure levels of IgG antibodies to VSAs of five heterologous and one homologous P. falciparum parasite isolates, and to two PfEMP1 DBLβ domains in blood samples collected a day before the challenge and 14 days after infection. We also measured the ability of an individual’s plasma to inhibit the interaction between PfEMP1 and ICAM1 using competition ELISA. We then assessed the association between the antibody levels, function, and clinical outcome during a 21-day follow-up period post infection using Cox proportional hazards regression. Results: Antibody levels to the individual isolate VSAs, or to two ICAM1-binding DBLβ domains of PfEMP1, were not associated with a significantly reduced risk of developing parasitemia or of meeting treatment criteria after the challenge after adjusting for exposure. However, anti-VSA antibody breadth (i.e., cumulative response to all the isolates) was a significant predictor of reduced risk of requiring treatment (HR 0.23 (0.10-0.50) p= 0.0002). Conclusion: The breadth of IgG antibodies to VSAs, but not to individual isolate VSAs, is associated with protection in CHMI.